Identification and Characterization of Panama Wilt Causing Fungal Isolates to Musa Paradisiaca cv. Puttabale - Venkatesh, Dr; Krishna, Venkatarangaiah; Pradeepa, Krishnappa; Rajanna, Santosh Kumar S; Nagaraja, Deeplanaik; Kumar, Mohan; Kumar, Santhosh (International Journal of Applied Sciences and Biotechnology, 2014)
Musa paradisiaca L. (Musaceae) cultivar ‘Puttabale’ is an indigenous banana commonly cultivated in the farmyards of Chitradurga,Davanagere, Chikmagalur and Shivamogga district of Karnataka. The fruits are valued for delicious taste. This banana cultivar is highlysusceptible to Fusarium infection and the yield loss has estimated to 30-40% at standing stage. The corm tissue of Musa paradisiaca cv.Puttabale showing typical panama wilt symptoms were collected from pathogen infected banana farmyard of Bhadravati, Sagara, Shikaripura,Holehonnur, Soraba, Thirthahalli, Gonibeedu and Lakkavalli regions of Shivamogga district of Karnataka. These infected corms were cultureon PDA medium and examined carefully by morphological and molecular identification. Out of the eight fungal isolates, the colonies of fungalisolates collected from Bhadravati, Sagara, Holehonnur, Thirthahalli, Gonibeedu and Lakkavalli regions produced a dense white aerialmycelium that evenly spread on the growth medium similar to the colony texture of Fusarium species. Among these fungal isolates, thepathogen collected from Gonibeedu region showed the presence of sickle or rod shaped, four-celled macro conidiophores, round or ovalshaped chlamydospores and the BLASTn search result showed 99 % similarity with the sequences of Fusarium oxysporum f. sp. cubense(Foc). The only one fungal isolate showed the presence of actual panama wilt causing fungi.DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11135 Int J Appl Sci Biotechnol, Vol. 2(4): 420-425